Hailstorms in Northern Greece: Synoptic patterns and thermodynamic environment - Sioutas, M.V.a; Flocas, H.A.b (Theoretical and Applied Climatology, 2003)
The synoptic scale atmospheric circulation prevailing during hail days in Northern Greece is examined for a period of 26 years (1976-2001) during the warm season. The initial objective of this classification scheme is to serve as a predictive tool for hail forecasting and permit a specification of greater or lesser hail risk, within the forecast activities of the Greek National Hail Suppression Program. The atmospheric circulation was classified into seven synoptic types and their frequency distribution was examined on an annual and monthly basis. Southwesterly flow (SW) and Shortwave trough (SWT) appear to be the most conducive synoptic types for hailstorm activity. Furthermore, the thermodynamic environment favoring the hailstorm development and evolution was examined using selected instability indices. The frequency distribution of the instability indices for a period of 11 years (1991-2001) in association with the synoptic types demonstrated their performance as a forecasting aid for thunderstorm activity to occur in a given synoptic environment.
Keywords: atmospheric circulation; Greece; hail; storm; Synoptic meteorology; thermodynamics; weather forecasting